Communication sheet eases barriers for Japanese patients and health professionals - Kento Sonoda; Teiichi Takedai; Cynthia Salter (BMC, 2022)
Abstract Background Language and cultural barriers can affect healthcare outcomes of minority populations. However, limited data are available on communication tools developed to address health disparities resulting from language and cultural barriers. Our study aimed to reduce communication barriers between Japanese patients and non-Japanese-speaking clinic staff by developing a Japanese-English Communication Sheet (JECS) to create more equitable clinical environments for Japanese patients in ambulatory care. Methods This study was conducted at a family health center in a United States urban setting, in the city of Pittsburgh, between November 2019 and August 2020. This study included Japanese adult patients who had health care office visits with one of two Japanese-speaking physicians and who completed a survey about the JECS. The JECS, written in Japanese and English, targets common sources of confusion by presenting common health questions, written in Japanese, and by explaining differences between common healthcare processes in Japan and the United States. Clinic staff who used the JECS with Japanese-speaking patients also were surveyed about the tool. Results Sixty Japanese patients met inclusion criteria and completed the survey. More than half of participants found the JECS useful, and those with self-reported limited English proficiency were most likely to report that the JECS was useful (p = 0.02). All nine non-Japanese speaking staff surveyed found the sheet helpful. Conclusions The JECS is a useful communication tool for addressing common barriers faced by Japanese patients seeking care at an American health center where Japanese-speaking physicians work but no clinic staff speak Japanese. A focused communication sheet can facilitate communication between patients and clinic staff and also reduce health inequities resulting from linguistic and cultural barriers. Additionally, using a communication sheet can advance quality and safety of patient care at the individual and institutional level.